Magnitude and factors associated with appropriate complementary feeding among children 6-23 months in Northern Ghana - Saaka, M.; Larbi, Asamoah; Mutaru, S.; Hoeschle-Zeledon, Irmgard (Springer, 2016)
Background: Inappropriate complementary feeding is a major contributor to child malnutrition. Previous studies have described complementary feeding practice using single indicators but a combination of indicators is needed to better explain the role of complementary feeding practices in child growth. To adequately quantify appropriate complementary feeding, we used a composite indicator comprising three of the World Health Organization (WHO) core infant and young child feeding (IYCF) indicators that relate closely to complementary feeding.